The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.4187/respcare.10349
|View full text |Cite
|
Sign up to set email alerts
|

Practical Guide to Management of Long-Term Noninvasive Ventilation for Adults With Chronic Neuromuscular Disease

Abstract: Recent technological advances in respiratory support and monitoring have dramatically enhanced the utility of long-term noninvasive ventilation. Improvements in quality of life and prolonged survival at home have been demonstrated for several common chronic neuromuscular diseases. Many adults with progressive neuromuscular respiratory disease can now comfortably maintain normal ventilation at home to near total respiratory muscle paralysis without needing a tracheostomy. However, current practice in many commu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 172 publications
(229 reference statements)
0
4
0
Order By: Relevance
“…[25][26][27][28][29][30] Using positive and negative framing can support the clinician in conveying prognostic information 26,30 as well as support patients' prognostic awareness. 29 Patients are often receptive to the dual approach 31 preferring phrases with hope/worry statements when discussing prognostic information. 32 Importantly, consideration of the patient's need for prognostic information is shown by asking if the patient wants to know what the clinician thinks about their illness (physicians) or health (nurses) now and in the future.…”
Section: Discussionmentioning
confidence: 99%
“…[25][26][27][28][29][30] Using positive and negative framing can support the clinician in conveying prognostic information 26,30 as well as support patients' prognostic awareness. 29 Patients are often receptive to the dual approach 31 preferring phrases with hope/worry statements when discussing prognostic information. 32 Importantly, consideration of the patient's need for prognostic information is shown by asking if the patient wants to know what the clinician thinks about their illness (physicians) or health (nurses) now and in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in line with previous EUROVENT data [1], other chronic lung diseases are treated with HMV. Despite guidelines [3,5] stating that carbon dioxide measurements (arterial blood gas or transcutaneous) are mandated in order to make a diagnosis of nocturnal hypoventilation-with recent data highlighting a targeted reduction in daytime and nocturnal carbon dioxide levels improving the patients' clinical outcome [6,7,[16][17][18][19][20]-the current survey showed that when initiating HMV and prior to discharge post initiation, the SpO 2 monitoring and physiological and ventilator downloaded data were employed more frequently than carbon dioxide measurements. Surprisingly, some respondents reported that they never use carbon dioxide measurements to titrate HMV.…”
Section: Tools To Assess Monitor and Manage Nocturnal Hypoventilationmentioning
confidence: 99%
“…Once established on HMV, the titration of HMV in patients with chronic respiratory failure should target a reduction in daytime PaCO 2 [6][7][8][9] and, therefore, a post initiation overnight assessment of both SpO 2 and TcCO 2 and daytime PaCO 2 are expected. Despite this recommendation, one HMV survey highlighted that clinicians expressed a low level of agreement with the investigations that are required prior to HMV prescription, with SpO 2 as the main driver for the initiation of HMV in chronic obstructive pulmonary disease (COPD) [10].…”
Section: Introductionmentioning
confidence: 99%
“…• Mechanical ventilation: Assisted ventilation (nocturnal noninvasive ventilation or invasive ventilation on tracheostomy) must be proposed as soon as diurnal and/or nocturnal alveolar hypoventilation appears (defined as pCO2 > 45 mmHg or TcpCO2 > 50 mmHg at night) [89].…”
Section: Respiratory Managementmentioning
confidence: 99%